From Normal Schools to Primary Teaching Schools: historic journey of primary teachers’ training schools - Sousa Pintassilgo, Joaquim António; Mogarro, Maria João (Historia y Memoria de la Educación, 2015)
This article provides a brief outline of the teacher training schools in Portugal for what was traditionally known as primary education, starting in the second half of the nineteenth century, when such schools began functioning regularly. Initially know as Primary Normal Schools, these institutions were renamed in 1930 to Primary Teaching Schools. In the second half of the 1980s, under full democracy, they were phased out, their place being taken by the Higher Schools of Education. In this article we seek to chronicle their evolution with a set of reflections on the ideals professed in their day, which are to be found primarily in training contexts and in textbooks. These principles deal mainly with such issues as the social roles to be played by the primary school teachers, the values inherent to the profession, pedagogical options considered to be legitimate and educational practices thought to be exemplary. We will analyse in particular the importance that the conceptions of the New School had in the construction of identity references during the republican period and their appropriation by the conservative pedagogy that circulated in the New State. We will also take into account the process of feminization, which left its own mark on the development of this teaching sector. Finally, we will outline a model of analysis for training institutions, using as our reference the case of Portugal.